A review of hypogonadotropic hypogonadism cases followed up in our clinic in the last decade. Issue 1 (February 2021) - Yılmazel, Fatih Kürşat; Karabulut, İbrahim and Yılmaz, Ali Haydar and Keskin, Ercüment and Bedir, Fevzi and Özbey, İsa
Introduction: The aim of the present study was to evaluate, with this retrospective study, the patients with hypogonadotropic hypogonadism, who were followed up in our clinic in the last decade and were reviewed in terms of the incidence of the disease, diagnostic methods and differential diagnoses, treatment modalities, fertility rates, and treatment success. Methods: After a very careful differential diagnosis, 81 patients (1.5% of infertile men presenting to the outpatient clinic) were diagnosed with hypogonadotropic hypogonadism. This study only included patients diagnosed with idiopathic hypogonadotropic hypogonadism. The treatment was undertaken in two periods depending on whether or not the patients wanted to have children at that time: testosterone replacement therapy and gonadotropin therapy. To induce spermatogenesis, the patients were treated using human chorionic gonadotropin and urinary or recombinant follicle-stimulating hormone. Results: The pregnancy rates of the spouses of the patients were as follows: spontaneous 64.6% (n = 42), intrauterine insemination 12.3% (n = 8), in vitro fertilization 15.3% (n = 10), and microscopic testicular sperm extraction + intracytoplasmic sperm injection 4.6% (n = 3). Conclusion: Idiopathic hypogonadotropic hypogonadism is a rare but easily diagnosable and treatable cause of male infertility. After a long period of the treatment, almost all idiopathic hypogonadotropic hypogonadism patients can be treated with gonadotropins (human chorionic gonadotropin + follicle-stimulating hormone) in order to have children. The most important issue in the treatment is the dose of the drugs used in the treatment and the duration of the treatment. The most important result is that the required gonadotropin dose varies according to each patient. Therefore, the treatment dose and duration should be increased until patients have children.